RSPO, ISPO and Global Environmental Governance: An English School Perspective - Yani, Yanyan Mochamad; Robertua, Verdinand (Jurnal Hubungan Internasional, 2017)
This is a theoretical and conceptual review focusing the role and influence of non-governmental organizations (NGOs) in global environmental governance (GEG). This research will use the case of the relationship between Indonesia Sustainable Palm Oil (ISPO) and Roundtable Sustainable Palm Oil (RSPO). RSPO is established in 2004 acted as private self-regulation in standard setting of palm oil trade in accordance with global environmental conservation values. In 2011, Government of Indonesia established ISPO to compete with RSPO. This research aimed to contribute to the development of theory of environmental studies of English School through the reformulation of pluralism and solidarism and to understand the relationship between pluralism and solidarism. This research has three conclusion. Firstly, despite RSPO and ISPO have different characters and procedures but they have similarities in achieving betterment in environmental protection. Secondly, based on the difference between RSPO and ISPO, this research reformulate pluralism and solidarismâ€™s contribution toward environmental studies of English School. Thirdly, global environmental governance is possible to be the middle way concept capturing the coexistence between pluralism and solidarism.Â